Comparison of different procedures for serotyping aquatic birnavirus. - Novoa, B (1995)
The current classification of aquatic birnaviruses is based on seroneutralization assays with polyclonal antibodies. In this study a comparison of several procedures used for serotyping aquatic birnaviruses was made with 10 virus strains (4 reference strains from salmonids and 6 birnaviruses isolated from turbot [Scophthalmus maximus]). The relationships among the birnavirus strains were studied by seroneutralization assay with polyclonal antibodies and by immunodot assay with both polyclonal and monoclonal antibodies. The results were compared with a presumptive classification obtained from analysis of restriction enzyme patterns of cDNA products obtained by PCR amplification. No correlation was found among the results obtained by the different procedures. The seroneutralization and the immunodot assays with polyclonal antibodies were not useful in classifying these birnaviruses strains; however, patterns of reaction with monoclonal antibodies emphasized the individuality of the strains, particularly in the case of two strains (231 and 460) whose patterns did not correspond to established serotypes. The application of PCR and restriction enzyme analysis is a promising system for approaching the classification of this viral group on the basis of genomic differences and similarities. The variable results obtained in this comparison lead us to think that the current classification of aquatic birnavirus may not be the most accurate and there is a need for modification incorporating recent isolates, not only from salmonid species but also from marine fish.